Elite murder and popular resistance: Evidence from post-World War II Poland - Krzysztof Krakowski; Max Schaub (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Does repression of opposition elites prevent resistance against foreign-imposed regimes? On the one hand, elimination of elites can undermine the opposition's capacity for antiregime resistance. Yet killing opposition elites deprives the new regime of useful human capital. Co-optation of elites becomes a tempting alternative. We examine this trade-off by studying the effects of elimination vis-à-vis survival of Polish elites during World War II. Our focus is on the Polish nobility, intellectuals, and (reserve) army officers. We exploit plausibly random variation in the officers' wartime deployment and subsequent imprisonment. While most officers in Nazi captivity survived, almost all those in Soviet captivity were murdered. We find that municipalities with more surviving elites saw fewer protests against the postwar Soviet-backed regime during the Solidarnosc-led uprising in the 1980s. Historical evidence suggests that surviving elites positively influenced local-level economic development, thereby reducing economic hardship and grievances against the regime.
Keywords: D74; F51; H56; 330; elites; repression; war; World War II; Poland